Public Perception in the Development of Curug Parigi Tourism of Bekasi City, Indonesia - Siti Hardiyanti; Fathan Tibyan Rahman (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2023)
The development of Curug Parigi tourism in Bekasi City is intended to create a beautiful Bekasi City tourism and build a better community economy. This research aims to discover the mechanism for developing Curug Parigi tourism in Bekasi City and the results of Curug Parigi tourism development in Bekasi City. The theory used in this study is the theory of modernization development from Alex Inkeles and David H. Smith as the core theory and Talcott Parsons' structural-functional theory as the operational theory, as a foundation function to understand and strengthen conditions or phenomena in the field. This study uses a qualitative descriptive method that describes and explains the area. Using observational data collection techniques, in-depth interviews, documentation, and literature studies in the Cikiwul Village. The data analysis was carried out using qualitative data analysis. The results of this study indicate that the entry of industrialization in the city of Bekasi in 2000 did not necessarily make the community progress and get used to the changes that occurred in their lives. It took years to adapt to modern life so that after people get used to changing, they can utilize and develop natural potential, namely Curug Parigi. The development of Curug Parigi invites many perceptions in society. Many people are happy with the result of the beautiful Parigi waterfall. There are also many people's opinions who are disappointed because the development of the Parigi waterfall is not perfect because the facilities needed in a tourist attraction have yet to be fulfilled.